Immunogenicity and safety of a tri-antigenic versus a mono-antigenic hepatitis B vaccine in adults (PROTECT): a randomised, double-blind, phase 3 trial. Issue 9 (September 2021) - Vesikari, Timo; Langley, Joanne M; Segall, Nathan; Ward, Brian J; Cooper, Curtis; Poliquin, Guillaume; Smith, Bruce; Gantt, Soren; McElhaney, Janet E; Dionne, Marc; van Damme, Pierre; Leroux-Roels, Isabel; et al.
Summary: Background: The seroprotection rate (SPR) of hepatitis B vaccination in adults is suboptimal. The aim of this study was to compare the SPR of a tri-antigenic hepatitis B vaccine (TAV), with a mono-antigenic vaccine (MAV) in adults of all ages. Methods: This was a multicentre, double-blind, phase 3, randomised controlled trial (PROTECT) comparing the immunogenicity and safety of TAV with MAV in 28 community and hospital sites in the USA, Finland, Canada, and Belgium. Adults (aged ≥18 years) seronegative for hepatitis B virus (HBV), including those with well-controlled common chronic conditions, were randomly assigned (1:1) and stratified by study centre and age according to a web-based permuted blocked randomisation. Participants received either TAV or MAV which were administered as an intramuscular dose (1 mL) of TAV (10 μg; Sci-B-Vac, VBI Vaccines [SciVac, Rehovot, Israel]) or MAV (20 μg; Engerix-B [GlaxoSmithKline Biologicals, Rixensart, Belgium]) on days 0, 28, and 168 with six study visits and 24 weeks of follow-up after the third vaccination. Participants, investigators, and those assessing outcomes were masked to group assignment. The co-primary outcomes were to show non-inferiority of the SPRs 4 weeks after the third vaccination with TAV versus MAV in adults aged 18 years and older, as well as superiority in adults aged 45 years and older. SPR was defined as the percentage of participants attaining anti-HBs titres of 10 mIU/mL or higher. Non-inferiority of TAV to MAV was concluded if the lower limit of the 95% CI for the between-group difference was greater than −5%. Non-inferiority was assessed in the per-protocol set of participants (aged ≥18 years) and superiority was assessed in all participants (aged ≥45 years) who received at least one vaccination and had at least one evaluable immunogenicity sample after baseline (full analysis set). Safety analyses were a secondary outcome and included all participants who received at least one injection. This trial is registered at Clinicaltrials.gov (NCT03393754 ) and EudraCT (2017–001819–36) and is closed to new participants. Findings: Between Dec 13, 2017, and April 8, 2019, 1607 participants (796 allocated to TAV and 811 allocated to MAV) were randomly assigned and distributed across age cohorts of 18–44 years (299 of 1607; 18·6%), 45–64 years (716 of 1607; 44·6%), and 65 years and older (592 of 1607; 36·8%). In participants aged 18 years and older, SPR was 91·4% (656 of 718) in the TAV group versus 76·5% (553 of 723) in the MAV group (difference 14·9%, 95% CI 11·2–18·6), showing non-inferiority in the per-protocol set. In participants aged 45 years and older, SPR was 89·4% (559 of 625) in the TAV group versus 73·1% (458 of 627) in the MAV group (difference 16·4%, 95% CI 12·2–20·7), showing superiority in the full analysis set. TAV was associated with higher rates of mild or moderate injection site pain (63·2% [503 of 796] in TAV vs 36·3% [294 of 811] in MAV), tenderness (60·8% [484 of 796] in TAV vs 34·8% [282 of 811] in MAV), and myalgia (34·7% [276 of 796] vs 24·3% [197 of 811] in MAV). Otherwise, the safety profile of TAV was similar to that of MAV. Interpretation: The safety and efficacy of TAV shows its usefulness for the prevention of HBV infection in adults, including those with stable and controlled chronic conditions. Funding: VBI Vaccines.